Clitoral priapism and persistent sexual arousal syndrome in women - Błażejewska, Anita; Lew-Starowicz, Zbigniew; Bińkowska, Małgorzata (Menopause Review/Przegląd Menopauzalny, 2008)
The purpose of this article is to describe how to act with a patient with an unusual sexual health condition, such as persistent sexual arousal syndrome or clitoral priapism. This is a real problem for clinicians, especially because of the limited data on the epidemiology, pathophysiology, diagnosis and treatment of syndromes like those.